Clinical Inertia: A Critique of Medical Reason - Reach, Gérard (Springer, 2015)
Clinical practice guidelines were initially developed within the context of evidence-based medicine with the goal of putting medical research findings into practice. However, physicians do not always follow them, even when they seem to apply to the particular patient they have to treat. This phenomenon, known as clinical inertia, represents a significant obstacle to the efficiency of care and a major public health problem, the extent of which is demonstrated in this book.